ISLAMIC ENTREPRENEURSHIP IDENTITY IN THE INDONESIAN HIJRAH COMMUNITY - Kunaifi, Aang; Djamaluddin, Burhan; Fauzia, Ika Yunia; Ritonga, Iskandar; Nurhayati, Nurhayati; Syam, Nur; Widiastuti, Tika; Ahsan, Muhamad (Multifinance, 2024)
This research aims to describe how Islamic entrepreneurship is implemented in the Hijrah community as a model that represents the identity of each community. The research was conducted using qualitative methods with a case study strategy. Data collection was carried out using observation, interviews, and documentation techniques. The research subjects were the Indonesian Muslim Entrepreneurs Community (KPMI), the Muslim Entrepreneurs Alliance (Assalim), and the Indonesian Business Islamic Boarding School (PBI). Data was collected from field observations and participant observations. There were 22 informants interviewed in-depth, three of whom were experts. Informants came from several regions, including Java, Sumatra, Bali, NTB, Sulawesi, and Kalimantan. The resulting documentation is in the form of brochures, photos of community activities, and digital information on websites, Facebook, Instagram, and WhatsApp groups. Data analysis was carried out by deducing theoretical propositions regarding the implementation of Islamic entrepreneurship in the hijrah community and developing them inductively to describe new findings and propositions. Based on the research results, it was found that the hijrah community implemented Islamic entrepreneurship in various identities, namely salaf-preneurship in the KPMI community, ideo-preneurship in the Assalim community, and spiritual-preneurship in the PBI community. The implication of this research is the development of Islamic entrepreneurship theory, which can be implemented widely by society.